Implementation of the Model View Controller Method in the BKPM Health Services Information System Prabumulih City - Desnia Angelia; Muchlis; Fajriyah (Yayasan Kita Menulis, 2024)
The community Lung Health Center is a health service facility than organizes and provides basic medical services at BKPM which are still carried out manually greatly slow down officers in managing data and searching for patient data. This research aims to design and develop a service system. The develipment method used is RAD (Rapid Application Development) which consists of requirements planning, design and implementation processes. The language used is PhpMySql, a base operation that allows selecting data or entering data that can be easily carried out automaticaly.